Analisis Strategi Pemasaran untuk Meningkatkan Volume Minat Nasabah dalam Bertransaksi Produk Gadai Emas IB pada PT. BPRS Sarana Prima Mandiri Pamekasan - Fariyanti, Nurul; Makhtum, Ahmad (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The aim of this research is to find out how PT. BPRS Sarana Prima Mandiri Pamekasan to increase customer interest in using and pawning their gold at PT. BPRS Sarana Prima Mandiri Pamekasan, This research uses research or a qualitative approach where the approach uses direct field research (field research), to reach PT's market targets. BPRS Sarana Prima Mandiri Pamekasan uses the marketing mix method, where there are 4Ps, namely; a. Product Strategy (Product), b. Price Strategy (Price), c. Place Strategy, d. Promotion Strategy (Promotion). As well as using or putting up banners and also collaborating with agencies, as well as house to house, namely establishing relationships at individual homes through pawn marketing. From the various methods mentioned above, PT. BPRS Sarana Prima Mandiri Pamekasan is able to increase financing, especially Pawn Gold iB and is also able to compete with surrounding agencies.